Efektivitas Model Pembelajaran Problem Based Learning (PBL) terhadap Prestasi Belajar Matematika Ditinjau dari Adversity Quotient (AQ) - Lusiana, Restu; Suprapto, Edy; Sukristini, Ika (Edumatica : Jurnal Pendidikan Matematika, 2021)
Innovative learning models have an influence on student achievement. This study aims to determine whether the PBL learning model is more effective than the STAD learning model (learning model that has been applied in schools) on mathematics learning achievement, whether there is a difference in the effect of the AQ of climber, camper, and quitter category students on mathematics learning achievement, and whether there is the interaction between the learning model and students' AQ on mathematics learning achievement. This research is in the form of quantitative research. The sample was taken using a simple random sampling technique where the experimental class was taught using the PBL learning model and the control class was taught using the STAD learning model. The data collection technique used the Questionnaire method for AQ data and the test method for students' mathematics learning achievement data. The data technique used a two-way unequal cell analysis of variance test with a 2Ã—3 matrix and a further test using the Scheffe test. The results of hypothesis testing with a significance level (Î±) = 5% indicate that there is a difference in the effect of the learning model on mathematics learning achievement (Fobs=19.97 and FÎ±=4.13), there are differences in the effect of each AQ category on mathematics learning achievement (Fobs=94.59 and FÎ±=3.28), and there is no interaction between the learning model and students' AQ on mathematics learning achievement (Fobs=2.39 and FÎ±=3.28).